Hartbeesthoek Radio Astronomy Observatory (HartRAO) Pioneering Advantage: Exploring Scientific Instrumentation Co-Location Benefits in Ensuring African Research Facility Sustainability - Madlanga, Simphiwe (Department of Electrical Engineering, 2024)
This study focuses on the prospect of development of radio astronomy facilities with instrument co-location capacity in the 8 Square Kilometre Array (SKA) African Very Long Baseline Interferometry Network (AVN) partner countries. The premise of the research is that the Hartebeesthoek Radio Astronomy Observatory (HartRAO) had laid down a blue-print and is well-suited as a proof of concept on what may be possible for the other countries. The technology gap between HartRAO, South Africa and the planned sites in the other countries is far better than between those countries and any others beyond the borders of the African continent. The fact that the countries of interest are all in sub-Saharan Africa fosters a level of mutual understanding where developmental challenges are concerned, but some of unique challenges are not to be underestimated. The research is qualitative and has been framed through the perspective of subjectivism and interpretivism, in order to do justice to the regional contexts and unique realities and circumstances in the development narrative. Research and data collection is pursued through the heterodox avenue of archival research; the collection and use of official organizational reports, archived material and even digital resources. Afri lagging, and no nation has been able to achieve much alone. The research shows how a large scientific project to introduce research capacity and infrastructure can be leveraged to respond to and incorporate some of the SDGs; namely SDG4 (quality education), SDG9 (Industry, innovation and infrastructure) and SDG 17 (Partnerships for the goals). Given the fast-approaching 2030 deadline for the S